Endostatin and osteopontin are elevated in patients with both coronary artery disease and aortic valve calcification. (December 2015) - Sponder, Michael; Fritzer-Szekeres, Monika; Litschauer, Brigitte; Binder, Thomas; Strametz-Juranek, Jeanette
Abstract: Background: The angiostatic factor endostatin (ES) plays an important role as mediator of angiogenesis. Elevated osteopontin (OPN) was associated with valve calcification in healthy individuals. The present study aimed to investigate ES and OPN levels in patients with both coronary artery disease (CAD) and aortic valve calcification (AVC). Methods and results: In total 224 non- or ex-smoking patients (161 male, mean age: 61.09 ± 11.02 years; 63 female: mean age: 67.49 ± 7.87 years) with angiographically verified and quantified CAD were recruited. Serum ES and plasma OPN levels were measured by ELISA and AVC was evaluated by a parasternal short axis view and quantified as non-, mild or moderate/severe. There was a stepwise increase of ES measurable with increasing severity of AVC, independent from age, BMI and CAD-severity (p = 0.018; F = 4.09). OPN also increased significantly with the grade of AVC severity (p = 0.029; F = 3.61) but was no longer significant when the co-variables (p = 0.31; F = 1.18) were inserted. Conclusions: This is the first study showing an association of ES with AVC in CAD-patients independent from age, BMI and CAD-severity which seems to be of distinct interest when trying to understand the process of heart valve calcification. OPN also correlates with AVC-severity but is mostly dependent on the age of the patients.